Microcomputer engineering - Miller, Gene H. (Prentice Hall, 1998)
A complete textbook and laboratory/homework manual for sophomore/junior-level courses in Microcomputers. This text focuses on microcomputers and microprocessors used as control devices (e.g., the Motorola 68HC11). Extensive material on using the Motorola M6HC11EVB and M68HC11EBU Trainers.